Syneresis and delayed detachment in agar plates1. Issue 18 (14th May 2015) - Divoux, Thibaut; Mao, Bosi; Snabre, Patrick
<x xml:space="preserve">Abstract</x> Gels in agar plates often lose contact with the dish sidewall as a result of syneresis and water evaporation. We rationalize such delayed and sudden detachment by means of direct observations and speckle correlation spectroscopy.